Fires reshape species-specific drought resilience of typical conifers in southwestern China - Peiyao Tao; Fen Zhang; Tian Chen; Xinglin Huang; Feifei Zhou; Keyan Fang; Xiaohua Gou; Yifei Zhao (Forest Ecology and Management, 2026)

Frost safety margin at the northern boundary of the sugar maple distribution: Implications for assisted migration - Jiani Gao; Roberto Silvestro; Sylvain Delagrange; Keyan Fang; Sergio Rossi (Forest Ecology and Management, 2026)

Distinct seasonality and trends of natural and anthropogenic wildfires in boreal forests - Cong Gao; Jinbao Li; Keyan Fang; Xu Zhang; Qi Zhang; Chunming Shi (Agricultural and Forest Meteorology, 2026)

Progressive scale convolutional network for spatio-temporal downscaling of soil moisture: A case study over the Tibetan Plateau - Ziyu Zhou; Keyan Hu; Ling Zhang; Zhaohui Xue; Yutian Fang; Yusha Zheng (Journal of Hydrology, 2026)

Orbitally driven sea surface temperature changes during the mid- to late Holocene: A global picture - Zanchenling Wang; Baoqi Huang; Jianghui Du; Keyan Fang; Xiaosong Chen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Interdecadal winter temperature variability driven by the East China Sea Mode: A global perspective - Keyan Fang; Hao Wu; Shuheng Lin; Jun Cheng; Jane Liu; Deliang Chen; Jinbao Li; Cesar Azorin-Molina; Zheng Zhao; Frode Stordal; Shuo Hao; Nicole Davi; et al. (Science China Earth Sciences, 2026)

Elevation dependence of vegetation phenology on the southeastern margin of the Tibetan Plateau - Tiantian Yang; Zheneng Hu; Wanxiong Zhang; Jingjing Wang; Zhongshi Zhang; Keyan Fang; Xin Zhou; Jie Zhou; Zhuoya Zhang; Zhengtang Guo (Science China Earth Sciences, 2026)

AgriFM: A multi-source temporal remote sensing foundation model for Agriculture mapping - Wenyuan Li; Shunlin Liang; Keyan Chen; Yongzhe Chen; Han Ma; Jianglei Xu; Yichuan Ma; Yuxiang Zhang; Shikang Guan; Husheng Fang; Zhenwei Shi (Remote Sensing of Environment, 2026)

Tree-ring δ18O reveals a consistent decrease in April precipitation in southeastern China since the 1950s and its linkage to global climate phenomena - Fang Wang; Guoliang Lei; Chotika Muangsong; Binggui Cai; Miaofa Li; Keyan Fang; Nathsuda Pumijumnong; Rattanakorn Chatwatthana; Shankar Panthi (Global and Planetary Change, 2026)

The Spring-Autumn and Warring States period coldness (400–350 BCE) contributed to the social unrest evidenced from coffin tree rings in southeastern China - Min Zhou; Zhongcai Xiao; Xin Jia; Xuanbo Wang; Liangsai Zhu; Feifei Zhou; Di Zhang; Zepeng Mei; Mengling Liu; Xinyuan Kong; Keyan Fang (Quaternary Science Reviews, 2025)

Multi-sensor multi-dimensional data fusion method for submarine cable anchor damage event identification - Chunying Xu; Xinjie Wu; Jingqi Fang; Jianrong Chen; Keyan Xiao; Jiawang Chen; Chuliang Wei; Hailun Fu (Ocean Engineering, 2025)

Tree-ring indicators of near-surface wind speed in the Poyang Lake area of monsoonal China - Min Zhou; Keyan Fang; Maowei Bai; Feifei Zhou; Yao Chen; Di Zhang; Wanru Tang; Zepeng Mei; Cesar Azorin-Molina (Dendrochronologia, 2025)

Winter-spring temperature reconstructed from tree-ring earlywood blue intensity in southern Anhui province of China - Kunyu Peng; Keyan Fang; Feifei Zhou; Jiani Gao; Zhipeng Dong; Maowei Bai; Zhuangpeng Zheng (Quaternary Science Reviews, 2025)

Coffin timber from southeastern China as a tree-ring archive for paleoclimate research - Zepeng Mei; Xin Jia; Duo Zheng; Feifei Zhou; Yu Xiao; Linping Ren; Wanru Tang; Di Zhang; Zhongcai Xiao; Min Zhou; Ting Guo; Xinyuan Kong; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Enhancing tree-ring visibility: A comparative study of sample and imaging techniques for 62 temperate tree species - Nela Altmanová; Martina Hrádková; Eva Návratová; Vít Pejcha; Václav Bažant; Savannah Collins-Key; Jiří Doležal; Daniel Druckenbrod; Tsutomu Enoki; Keyan Fang; Pavel Fibich; Grant L. Harley; et al. (Dendrochronologia, 2025)

Multidecadal modulation of multi-year El Niño events over the past millennium - Shuheng Lin; Keyan Fang; Hao Wu; Hanjie Fan; Feifei Zhou; Jinbao Li; Kaiqiang Deng; Hans W. Linderholm; Song Yang (Science China Earth Sciences, 2025)

An improved method for extracting cellulose from fossil wood and its paleoclimatic implications - Donghao Wu; Xin Wang; Yang Deng; Mi Wang; Gang Hu; Xuan Ding; Linlin Gao; Keyan Fang; Xiaohua Gou (Frontiers of Earth Science, 2025)

The first temperature reconstruction based on tree-ring blue intensity in the Qinling Mountains - Mei Xie; Qiufang Cai; Yu Liu; Keyan Fang; Qiuyue Zhou; Meng Ren; Kebayier Meng; Qiang Li; Changfeng Sun; Huiming Song; Dan Chen; Yufei Chen (Dendrochronologia, 2025)

The negative effects of competition on tree resilience weakened as drought severity intensified - Xinyu Han; Lushuang Gao; Xianliang Zhang; Keyan Fang; Sijie Li; Keda Cui; Mengzhao Guo; Xiuhai Zhao (Agricultural and Forest Meteorology, 2025)

Pluvial conditions increased the risk of debris flows over the southern Hengduan Mountains: Evidence from tree-ring blue intensity and historical documents - Qianlu Zhou; Keyan Fang; Feifei Zhou; Jiani Gao; Hao Wu (CATENA, 2025)

An Elevated Influence of the Low‐Latitude Drivers on the East Asian Winter Monsoon After Around 1990 - Bozhou Chen; Keyan Fang; Zepeng Mei; Tinghai Ou; Feifei Zhou; Hao Wu; Zheng Zhao; Deliang Chen (International Journal of Climatology, 2024)
Current East Asian winter monsoon (EAWM) indices effectively depict the associated high‐ and low‐latitude atmospheric circulations. However, the spatial dynamics of the winter coldness within the monsoon domain are not well adequately represented by EAWM indices. We introduce a novel approach to classify winter temperatures based on both their co‐variability and their mean values. We classified the EAWM domain into three distinct modes: northern (ranging from −27°C to −15°C), central (−14°C to 5°C), and southern (6°C to 27°C). The northern mode, characterised by intense coldness, correlates with a strengthened westerlies that traps Arctic cold air masses during the positive phase of the Arctic Oscillation (AO). In contrast, the southern mode is primarily influenced by low‐latitude oceanic and atmospheric patterns, particularly for near‐coast areas. The central mode, representing an interplay of both high and low‐latitude processes, encapsulates the comprehensive characteristics of the EAWM. Our analysis reveals a notable shift in the relationships among the northern, central, and southern modes around 1990. Prior to this year, the EAWM was predominantly influenced by northern atmospheric patterns, while there is a discernible increase in the influence of low‐latitude drivers afterwards. This shift may be linked to the significant warming in the western Pacific and Indian Oceans, underscoring the heightened role of low‐latitude drivers on the EAWM.

Deciphering the transfer of hydroclimate signals to tree-ring δ18O using a proxy system model in East Asia's Meiyu region - Yesi Zhao; Huayu Lu; Keyan Fang; Peng Zhang; Deliang Chen; Achim Bräuning; Jussi Grießinger; Bao Yang; Chenghong Liang; Hongyan Zhang; Yiqian Sun; Qing Jin; et al. (Chemical Geology, 2024)

July– August minimum temperature variability encoded in latewood blue intensity in southeastern China - Kunyu Peng; Feifei Zhou; Zhipeng Dong; Maowei Bai; Zhuangpeng Zheng; Keyan Fang (International Journal of Climatology, 2024)
Tree‐ring blue intensity (BI) is well known as a relatively new proxy, which has been utilized for temperature reconstructions over some regions of the worldwide, and has great research potential. In this study, based on tree‐ring data from Pinus massoniana in northwestern Wuyi Mountains in southeastern China, we established a series of tree‐ring width (TRW), earlywood BI (EWBI), latewood BI (LWBI) and delta BI (ΔBI) chronologies. The correlation analysis results indicated that BI chronologies are better than TRW chronology in relation to climate factors; EWBI chronology is a positive correlation with three temperatures (Tmean, Tmax and Tmin), whereas ΔBI and LWBI chronologies almost are negative correlations with temperatures. The LWBI chronology exhibited the highest correlation in July–August Tmin during 1955–2021 ( r = −0.61, p

Examining the effect of sample size on the estimation of low-frequency signals in tree-ring chronologies - Hao Wu; Keyan Fang; Xinyan Li (Dendrochronologia, 2024)

ENSO weakens the co-variability between the spring persistent rains and Asian summer monsoon: Evidences from tree-ring data in southeastern China - Feifei Zhou; Keyan Fang; Fredrik Charpentier Ljungqvist; Tinghai Ou; Jun Cheng; Fen Zhang; Zhengtang Guo (Journal of Hydrology, 2024)

Modulations of NAO on the interplay between monsoon and westerlies in Asia on interdecadal timescales - Qichao Yao; Ben Zheng; Keyan Fang; Amy Hudson; Feifei Zhou; Haonan Chen; Haiming Tan; Futao Guo; Valerie Trouet (Climate Dynamics, 2024)

Summer heat induced the decline of Pinus taiwanensis forests at its southern limit in humid Subtropical China - Feifei Zhou; Zhipeng Dong; Keyan Fang; Dongliang Cheng; Hui Tang; Tinghai Ou; Fen Zhang; Deliang Chen (Agricultural and Forest Meteorology, 2024)

Indian summer monsoon drives synchronous interdecadal hydroclimate changes in the Tibetan Plateau and surroundings - Keyan Fang; Zepeng Mei; Hao Wu; Feifei Zhou; Heikki Seppä; Zhengtang Guo (Global and Planetary Change, 2024)

Reconstruction of seasonal precipitation anomalies from tree-ring latewood records in southeastern China - Xinguang Cao; Pei-ken Kao; Hongbing Hu; Feifei Zhou; Di Zhang; Keyan Fang (Climate Dynamics, 2024)

Extracting operation rule of cascade reservoirs using a novel framework considering hydrometeorological spatiotemporal information based on artificial intelligence models - Wei Fang; Hui Qin; Keyan Shen; Xin Yang; Yuqi Yang; Benjun Jia (Journal of Cleaner Production, 2024)

Growth responses to climate warming and their physiological mechanisms differ between mature and young larch trees in a boreal permafrost region - Xi Qi; Paolo Cherubini; Kerstin Treydte; Mai-He Li; Zhengfang Wu; Hong S. He; Haibo Du; Keyan Fang; Matthias Saurer (Agricultural and Forest Meteorology, 2023)

Drought variations in the southeastern Tibetan Plateau region since 1704 and their link to the Atlantic Multidecadal Oscillation - Wanru Tang; Keyan Fang; Zepeng Mei; Feifei Zhou; Hao Wu; Kristina Seftigen; Xinguang Cao; Zhipeng Dong; Maowei Bai; Yao Chen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Quantification of soil erosion dynamics in the hilly red soil region of Southeast China based on exposed roots - Di Zhang; Feifei Zhou; Keyan Fang; Nicole Davi; Zhibiao Chen; Fei Wang; Yao Chen (CATENA, 2023)

Weakened western Pacific teleconnection pattern caused a decrease in spring persistent rainfall in north of 26°N over Southeast China - Yao Chen; Chongqing Wang; Feifei Zhou; Shixiong Jiang; Xi Li; Sunxian Weng; Xinyuan Wan; Rongyang Xiao; Qiang Liu; Keyan Fang (International Journal of Climatology, 2023)
The spring persistent rainfall (SPR) is a unique synoptic and climatic phenomenon before the onset of the Asian summer monsoon over Southeast China (SEC). The warming climate has caused notable interdecadal changes of various climate systems, such as the Asian summer monsoon. However, it is still unclear whether there is a regime shift within the SPR band. To fill this knowledge gap, the boreal spring (March–May) rainfall data across SEC from the Climate Research Unit TS 4.05 are used herein to reveal its spatio‐temporal variations for 1951–2019 with the empirical orthogonal function (EOF) analysis. The EOF1 pattern exhibits a spatial monotonic variability of the SPR over SEC, which is jointly impacted by the El Niño‐Southern Oscillation and the Arctic Oscillation. The EOF2 pattern, a south–north dipole pattern, highlights a marked decrease (increase) of the SPR approximately to north (south) of the 26°N. We find that the decrease in the northern SPR band is closely modulated by western Pacific teleconnection pattern (WPP). Recent weakening WPP is coincident with a decline of the East Asian subtropical jet over this area, causing anomalous descending motions and thus accounts for persistent decline of the SPR over north of 26°N.

Recovery of bio‑sulfur and metal resources from mine wastewater by sulfide biological oxidation-alkali flocculation: A pilot-scale study - Xin Hu; Hong Yang; Xiaoyue Fang; Tongyu Shi; Keyan Tan (Science of The Total Environment, 2023)

Reconstructed Jing River streamflow from western China: A 399-year perspective for hydrological changes in the Loess Plateau - Xiaoen Zhao; Keyan Fang; Feng Chen; Hadad Martín; Fidel A. Roig (Journal of Hydrology, 2023)

Rapid expansion of wetlands on the Central Tibetan Plateau by global warming and El Niño - Yang Li; Zhengyang Hou; Liqiang Zhang; Changqing Song; Shilong Piao; Jintai Lin; Shushi Peng; Keyan Fang; Jing Yang; Ying Qu; Yuebin Wang; Jingwen Li; et al. (Science Bulletin, 2023)

Increased amplitude of the North Pacific Gyre Oscillation towards recent: Evidence from tree‐ring‐based reconstruction since 1596 - Zhipeng Dong; Feifei Zhou; Zhuangpeng Zheng; Keyan Fang (International Journal of Climatology, 2022)
The North Pacific Gyre Oscillation (NPGO) is the second leading mode of the sea surface height (SSH) of the North Pacific Ocean, playing a key role in causing regional ecosystem changes and large‐scale climate anomalies. However, its long‐term evolution prior to the industrial era is largely unknown. This study provides a reconstruction of the NPGO from 1596 onwards from 19 NPGO‐sensitive tree‐ring chronologies in the Himalayan Mountains, the Rocky Mountains, the Coastal Mountains and the Alaskan Mountain Range, which explained 57.1% of the observed NPGO variations. The selected tree‐ring chronologies showed strong linkages with the NPGO but weak or no correlations with the Pacific Decadal Oscillation (PDO), another leading mode of the North Pacific Ocean. The reconstruction revealed that the NPGO variance and amplitude are not only the strongest towards recent in the instrumental period but also in the reconstruction period. The linkages between the NPGO and El Niño–Southern Oscillation (ENSO) became strengthened towards recent, which may be attributed to the increased occurrence of central Pacific ENSO during the anthropogenic warming period. In addition, close linkages were found between the NPGO and the multidecadal Pacific variability (MPV), the North Atlantic Oscillation (NAO), the Atlantic Multidecadal Oscillation (AMO) at the interannual and multidecadal scales, indicative of strong teleconnections between the ocean–atmosphere modes of the Pacific and Atlantic.

Improved spring temperature reconstruction using earlywood blue intensity in southeastern China - Xinguang Cao; Hongbing Hu; Pei‐ken Kao; Brendan M. Buckley; Zhipeng Dong; Xiuling Chen; Feifei Zhou; Keyan Fang (International Journal of Climatology, 2022)
Because instrumental observations are too short to fully represent long‐term natural variability, high‐resolution temperature proxy records are essential to understanding past climate and assessing current climate variability in the context of long‐term patterns. In the subtropics, progress in this field has been hampered by a relative lack of long and truly temperature‐sensitive proxy records. In this study, we provide an assessment of the dendroclimatic potential of blue intensity (BI) and ring‐width (RW) measurements from two hot/humid Pinus massoniana sites in China. Our results show that RW exhibits a significant ( p

Overestimated gains in water‐use efficiency by global forests - Xiao Ying Gong; Wei Ting Ma; Yong Zhi Yu; Keyan Fang; Yusheng Yang; Guillaume Tcherkez; Mark A. Adams (Global Change Biology, 2022)
Increases in terrestrial water‐use efficiency (WUE) have been reported in many studies, pointing to potential changes in physiological forcing of global carbon and hydrological cycles. However, gains in WUE are of uncertain magnitude over longer (i.e. >10 years) periods of time largely owing to difficulties in accounting for structural and physiological acclimation. 13 C signatures (i.e. δ 13 C) of plant organic matter have long been used to estimate WUE at temporal scales ranging from days to centuries. Mesophyll conductance is a key uncertainty in estimated WUE owing to its influence on diffusion of CO 2 to sites of carboxylation. Here we apply new knowledge of mesophyll conductance to 464 δ 13 C chronologies in tree‐rings of 143 species spanning global biomes. Adjusted for mesophyll conductance, gains in WUE during the 20th century (0.15 ppm year −1 ) were considerably smaller than those estimated from conventional modelling (0.26 ppm year −1 ). Across the globe, mean sensitivity of WUE to atmospheric CO 2 was 0.15 ppm ppm −1 . Ratios of internal‐to‐atmospheric CO 2 (on a mole fraction basis; c i / c a ) in leaves were mostly constant over time but differed among biomes and plant taxa—highlighting the significance of both plant structure and physiology. Together with synchronized responses in stomatal and mesophyll conductance, our results suggest that ratios of chloroplastic‐to‐atmospheric CO 2 ( c c / c a ) are constrained over time. We conclude that forest WUE may have not increased as much as previously suggested and that projections of future climate forcing via CO 2 fertilization may need to be adjusted accordingly.

The intra-annual intrinsic water use efficiency dynamics based on an improved model - Xiaojin Bing; Keyan Fang; Xiaoying Gong; Wenzhi Wang; Chenxi Xu; Maihe Li; Chaoyue Ruan; Weiting Ma; Yingjun Li; Feifei Zhou (Climatic Change, 2022)

Age-related growth responses of birch to warming along an elevational gradient on Changbai Mountain - Xi Qi; Keyan Fang; Haibo Du; Jianan He; Hongshi He; Zhengfang Wu (European Journal of Forest Research, 2022)

Complex network of synchronous climate events in East Asian tree-ring data - Xijin Wang; Fenghua Xie; Zhongshi Zhang; Stefan Liess; Keyan Fang; Chenxi Xu; Feng Shi (Climatic Change, 2021)

Co-varying temperatures at 200 hPa over the Earth’s three poles - Keyan Fang; Peng Zhang; Jingming Chen; Deliang Chen (Science China Earth Sciences, 2021)

Responses of the radial growth of the endangered species Keteleeria fortunei to climate change in southeastern China - Zheng Zhao; Keyan Fang; Chunfu Cao; Dai Chen; Xiaoyue Liang; Zhipeng Dong; Peng Zhang (Trees, 2019)

East Asian Summer Monsoon moisture sustains summer relative humidity in the southwestern Gobi Desert, China: evidence from δ18O of tree rings - Qiang Li; Yu Liu; Takeshi Nakatsuka; Keyan Fang; Huiming Song; Ruoshi Liu; Changfeng Sun; Gang Li; Ke Wang (Climate Dynamics, 2019)

Interdecadal modulation of the Atlantic Multi-decadal Oscillation (AMO) on southwest China’s temperature over the past 250 years - Keyan Fang; Zhengtang Guo; Deliang Chen; Lei Wang; Zhipeng Dong; Feifei Zhou; Yan Zhao; Jinbao Li; Yingjun Li; Xinguang Cao (Climate Dynamics, 2019)

An interdecadal climate dipole between Northeast Asia and Antarctica over the past five centuries - Keyan Fang; Deliang Chen; Zhengtang Guo; Yan Zhao; David Frank; Maosheng He; Feifei Zhou; Feng Shi; Heikki Seppä; Peng Zhang; Raphael Neukom (Climate Dynamics, 2019)

Intensified variability of the El Niño–Southern Oscillation enhances its modulations on tree growths in southeastern China over the past 218 years - Lei Wang; Keyan Fang; Dai Chen; Zhipeng Dong; Feifei Zhou; Yingjun Li; Peng Zhang; Tinghai Ou; Guoyang Guo; Xinguang Cao; Mingtong Yu (International Journal of Climatology, 2018)
Lack of long‐term tree‐ring records in the core regions of the Asian summer monsoon in southeastern China limits our ability of evaluating the current climate change in a historical context. In this study, we developed the first 218‐year tree‐ring chronology (1798–2015) of Pinus massoniana in Zhangping area, Fujian Province, humid subtropical China. This chronology is positively correlated with winter–spring (January–March) temperature ( r = 0.359, p r = 0.351, p r = 0.30, N = 66) matches closely with the ENSO variability during 1950–2015. The modulations of the ENSO on regional tree growth have been the most conspicuous since the 1950s, which corresponds to its enhanced inter‐annual variability. The extreme growth anomalies match quite well with the extreme years of the moisture‐sensitive chronologies. The dry epoch from 1935 to 1958 is the most severe long‐lasting drought in our tree rings, which is a widely distributed pattern in southeastern China and is likely modulated by the La Niña‐like modes in that period.

Drought variation of western Chinese Loess Plateau since 1568 and its linkages with droughts in western North America - Keyan Fang; Zhengtang Guo; Deliang Chen; Hans W. Linderholm; Jinbao Li; Feifei Zhou; Guoyang Guo; Zhipeng Dong; Yingjun Li (Climate Dynamics, 2017)

Interannual to centennial variability of the South Asian summer monsoon over the past millennium - Feng Shi; Keyan Fang; Chenxi Xu; Zhengtang Guo; H. P. Borgaonkar (Climate Dynamics, 2017)

Abrupt vegetation shifts caused by gradual climate changes in central Asia during the Holocene - Yan Zhao; YaoLiang Liu; ZhengTang Guo; KeYan Fang; Quan Li; XianYong Cao (Science China Earth Sciences, 2017)

Climate–growth relationships of Schrenk spruce (Picea schrenkiana) along an altitudinal gradient in the western Tianshan mountains, northwest China - Yuxia Huo; Xiaohua Gou; Wenhuo Liu; Jinbao Li; Fen Zhang; Keyan Fang (Trees, 2017)

Interdecadal moisture patterns and teleconnections in Monsoonal Asia over the past seven centuries - Feifei Zhou; Keyan Fang; Fen Zhang; Yingjun Li (International Journal of Climatology, 2017)
Interdecadal (10‐ to 100‐year oscillation) moisture variations over the Monsoonal Asia ( MA ) is highly variable across regions and time, which are relatively less understood due to the shortness of the instrumental data of a few decades. In this study, comprehensive investigations on the spatiotemporal distributions of the interdecadal moisture variations over MA as well as their evolution from prior to the industrial era were conducted utilizing the tree‐ring based drought reconstructions, i.e. the Monsoonal Asia Drought Atlas. Nine interdecadal moisture patterns in MA are identified using the self‐organizing map based on the ensemble empirical mode decomposition. To further investigate these interdecadal moisture patterns, we aggregated the selected nine nodes into four patterns using a hierarchical clustering approach. Among them, Pattern 1 stands for a teleconnection between the Northeast MA and the Indian Peninsula, and Pattern 2 represents a dipole pattern between the Southern and Northern MA . We find that Pattern 1 may be linked with the dynamics of the Antarctic Oscillation that can modulate the strength of the Asian summer monsoon through meridional teleconnections. Pattern 2 is mainly driven by the elevated El Niño‐Southern Oscillation variance and the zonal ‘Silk Road Pattern’ to bridge this interdecadal modulation.

Moisture increase in response to high-altitude warming evidenced by tree-rings on the southeastern Tibetan Plateau - Jinbao Li; Jiangfeng Shi; David D. Zhang; Bao Yang; Keyan Fang; Pak Hong Yue (Climate Dynamics, 2017)

Nonlinear characteristics of hydroclimate variability in the mid-latitude Asia over the past seven centuries - Feifei Zhou; Keyan Fang; Yingjun Li; Qiuyan Chen; Dan Chen (Theoretical and Applied Climatology, 2016)

Response of Pinus taiwanensis growth to climate changes at its southern limit of Daiyun Mountain, mainland China Fujian Province - Dan Chen; KeYan Fang; YingJun Li; ZhiPeng Dong; Yu Zhang; FeiFei Zhou (Science China Earth Sciences, 2016)

A multi-proxy reconstruction of spatial and temporal variations in Asian summer temperatures over the last millennium - Feng Shi; Quansheng Ge; Bao Yang; Jianping Li; Fengmei Yang; Fredrik Charpentier Ljungqvist; Olga Solomina; Takeshi Nakatsuka; Ninglian Wang; Sen Zhao; Chenxi Xu; Keyan Fang; et al. (Climatic Change, 2015)

Interdecadal hydroclimate teleconnections between Asia and North America over the past 600 years - Keyan Fang; Heikki Seppä; Deliang Chen (Climate Dynamics, 2015)

A reconstruction of the Asia‐Pacific Oscillation Index for the past 1500 years and its association with the Asian summer monsoon - Keyan Fang; Nicole Davi; Rosanne D'Arrigo (International Journal of Climatology, 2014)
There is a need to understand the long‐term variability Asian‐Pacific Oscillation ( APO ) due to its close linkages with large‐scale ocean–atmosphere anomalies. The first principal component ( PC ) of a network of 130 temperature proxies covering East Asia and the northeastern Pacific Ocean was employed to reconstruct the instrumental APO index from 500 to 2006. It explains 46.7% of the instrumental APO variance and correlates significantly with middle to upper tropospheric temperatures. The reconstructed APO reaches its peak in the Little Ice Age ( LIA ) and is low during the Medieval Climate Anomalies ( MCA ) period and since the 1850. The APO variations are caused by the temperature difference between East Asia and north Central Pacific Ocean. The Pacific Decadal Oscillations ( PDOs ) and tropical ocean‐atmospheric features [the El Niño–Southern Oscillation ( ENSO ) and the Indian Ocean Dipole ( IOD )] are reversely connected to APO variations particularly on long timescale (e.g. centennial timescale) and short timescale (e.g. interannual), respectively, possibly via modulating the strength of the Asian summer monsoon. However, the relationship between the APO and both external forcings (e.g. solar irradiation) and the PDO are quite variable, which is significant only when the influences of the coupled ocean‐atmosphere patterns are weakened. The APO is positively correlated with indices of the hydroclimate of Monsoonal Asia, and is negatively associated with climatic indices for western North America.

How robust are Holocene treeline simulations? A model–data comparison in the European Arctic treeline region - KEYAN FANG; JESSE L. MORRIS; J. SAKARI SALONEN; PAUL A. MILLER; HANS RENSSEN; MARTIN T. SYKES; HEIKKI SEPPÄ (Journal of Quaternary Science, 2013)
Treeline encroachments and retractions can provide global‐scale feedbacks to the climate system, and treeline dynamics are therefore of great relevance for understanding global climate variability. To assess the accuracy of long‐term treeline simulations based on the generalized dynamic vegetation model LPJ‐GUESS, we simulate European Arctic treeline dynamics over the past 9000 years and compare the results with fossil‐based reconstructions. The results show that while LPJ‐GUESS is limited in its ability to capture species‐level current treeline patterns and past dynamics, it is generally able to realistically simulate the Holocene coniferous treeline changes with a cutoff biomass carbon of 2 C kg m −2 . The model captures the northward expansion of the boreal forest during the mid Holocene and correctly simulates a treeline retreat in response to climate cooling during the last 3000 years. However, there are data–simulation disagreements particularly during the early Holocene, which mainly result from the differences between the two palaeoclimate model scenarios used to drive the simulations. We suggest that the spatial accuracy of the model could be improved by incorporating the influence of topographic features, the extent of the Arctic peatlands, the tree species life‐history characteristics, microclimate and other ecological factors. Copyright © 2013 John Wiley & Sons, Ltd.

Spatiotemporal variability of tree growth and its association with climate over Northwest China - Keyan Fang; Xiaohua Gou; Fahu Chen; Edward Cook; Jinbao Li; Yingjun Li (Trees, 2012)

Precipitation variability during the past 400 years in the Xiaolong Mountain (central China) inferred from tree rings - Keyan Fang; Xiaohua Gou; Fahu Chen; David Frank; Changzhi Liu; Jinbao Li; Miklos Kazmer (Climate Dynamics, 2012)

The impacts of permafrost change on NPP and implications: A case of the source regions of Yangtze and Yellow Rivers - Yiping Fang; Dahe Qin; Yongjian Ding; Jianping Yang; Keyan Xu (Journal of Mountain Science, 2011)

Tree growth and time-varying climate response along altitudinal transects in central China - Keyan Fang; Xiaohua Gou; Fahu Chen; Jinbao Li; Rosanne D’Arrigo; Edward Cook; Tao Yang; Wenhuo Liu; Fen Zhang (European Journal of Forest Research, 2010)

Spatial drought reconstructions for central High Asia based on tree rings - Keyan Fang; Nicole Davi; Xiaohua Gou; Fahu Chen; Edward Cook; Jinbao Li; Rosanne D’Arrigo (Climate Dynamics, 2010)

Reconstructed droughts for the southeastern Tibetan Plateau over the past 568 years and its linkages to the Pacific and Atlantic Ocean climate variability - Keyan Fang; Xiaohua Gou; Fahu Chen; Jinbao Li; Rosanne D’Arrigo; Edward Cook; Tao Yang; Nicole Davi (Climate Dynamics, 2010)

Tree‐ring based drought reconstruction for the Guiqing Mountain (China): linkages to the Indian and Pacific Oceans - Keyan Fang; Xiaohua Gou; Fahu Chen; Rosanne D'Arrigo; Jinbao Li (International Journal of Climatology, 2010)
We have reconstructed the Palmer Drought Severity Index (PDSI) from 1618 to 2005 for the Guiqing Mountain area, north central China, using tree rings of Pinus tabulaeformis . The reconstruction explains 49% of the actual PDSI variance during the common period 1951–2005. The PDSI reconstruction is representative of moisture conditions over a large area to the south and east of the sampling site, the core area for the 1997 severe drought. It shows slightly different variations when compared to other available PDSI reconstructions north and west of the sampling sites. The drought epoch since 1994 is most severe for our study region, with least intensity for the Helan Mountain area. The drought in 1997 was centered in the Guiqing Mountain area, and appears to be the most extreme drought event over the length of reconstruction. Significant spectral peaks are identified at 2.1, 2.3, 2.5, 3.2, 3.6, 42.7 and 53.8 years. Our reconstructed droughts are significantly correlated with sea surface temperature in the northern Indian Ocean, western equatorial Pacific Ocean, eastern equatorial Pacific Ocean, Eastern China Sea and Sea of Japan. The linkages to the Indian and Pacific Oceans suggest the connection of regional moisture variations to the Asian monsoon circulations. Copyright © 2009 Royal Meteorological Society

Response of regional tree-line forests to climate change: evidence from the northeastern Tibetan Plateau - Keyan Fang; Xiaohua Gou; Fahu Chen; Jianfeng Peng; Rosanne D’Arrigo; William Wright; Mai-He Li (Trees, 2009)

Drought reconstruction in the Qilian Mountains over the last two centuries and its implications for large-scale moisture patterns - Wenhuo Liu; Xiaohua Gou; Meixue Yang; Yong Zhang; Keyan Fang; Tao Yang; Liya Jin (Advances in Atmospheric Sciences, 2009)